2018
DOI: 10.1111/1748-5967.12278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fruit host on wing morphology in Drosophila suzukii (Diptera: Drosophilidae): A first view using geometric morphometrics

Abstract: The invasive alien fruit pest Drosophila suzukii, (Matsumura 1931) causes economic loss in soft‐skinned fruit production across Europe. After its first detection in 2008, the species has successfully expanded to a wide geographic area and invaded new host plants in a relatively short period of time. The aim of the present study was to analyze the connection between food preferences as host specialization and the morphology of D. suzukii. Population morphological variation in wings was investigated in two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…In this study, we showed a reliable pattern of differences in forewing shape related to orchard control practice type. Findings support previous work where phenotypic differences in wing shape and size were shown to be reliable population biomarkers [21,22,23,27,28,29,61,62]. From the data gathered in this study, it is clear that morphological differences are present in the forewing shape of CM based on control practices (ecological vs. integrated).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we showed a reliable pattern of differences in forewing shape related to orchard control practice type. Findings support previous work where phenotypic differences in wing shape and size were shown to be reliable population biomarkers [21,22,23,27,28,29,61,62]. From the data gathered in this study, it is clear that morphological differences are present in the forewing shape of CM based on control practices (ecological vs. integrated).…”
Section: Discussionsupporting
confidence: 89%
“…By applying GM analyses, detection of different biotypes of some other insects such as spotted wing drosophila [62], western corn rootworm [21,23], ground beetle [61], and beet root weevil [29] was confirmed as a diagnostic tool and consequently introduced into IPM practice. Here, field populations were investigated in detail by orchard control type, and differences in shape variation were found for CM.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous observations (Bitner-Mathé and Klaczko, 1999;Gilchrist et al, 2000;Gidaszewski et al, 2009;de Camargo et al, 2015;Siomava et al, 2016;Pieterse et al, 2017;Lemic et al, 2020;Rohner, 2020;Cortés-Suarez et al, 2021), we detected a clear sexual dimorphism in wing size and shape in all three species, which was most pronounced in C. capitata. Sexual dimorphism in wing shape is most likely functionally relevant because it is widespread in insects (Cowley et al, 1986;Pretorius, 2005;Bogdanović et al, 2009;Gidaszewski et al, 2009;Ribak et al, 2009;Allen et al, 2011;Benítez et al, 2011;de Camargo et al, 2015;Gallesi et al, 2015;Virginio et al, 2015;Lorenz et al, 2017;Rodríguez and Liria, 2017;Pajač Živković et al, 2018). In C. capitata and D. melanogaster, males and females differed mostly in wing width.…”
Section: Sexual Dimorphism In Wing Morphologymentioning
confidence: 99%
“…GM was tested as an existing method, though novel in its application, for morphological differences in field-insect pest populations versus laboratory populations and integrated versus ecological populations in Croatia. That is, Pajač Živković et al [137] revealed two noticeable wing shape morphotypes in Drosophila suzukii (i.e., vein configuration) between grape and strawberry crops. Different IPM practices in agro-ecosystems generate different degrees of disturbance in insect communities, as shown by Benitez et al [138] where shape variation and fluctuating asymmetry levels were estimated by applying GM methods to the beetle Pterostichus melas melas.…”
Section: Perspectives In Codling Moth Resistance Detectionmentioning
confidence: 99%